Energy Efficient Data Centers : Third International Workshop, E2DC 2014, Cambridge, UK, June 10, 2014, Revised Selected Papers - Klingert, Sonja; Chinnici, Marta; Rey Porto, Milagros; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Workshop on Energy Efficient Data Centers, E2DC 2014, held in Cambridge, UK, in June 2014. The 10 revised full papers presented were carefully selected from numerous submissions. They are organized in three topical sections named: energy optimization algorithms and models, the future role of data centres in Europe and energy efficiency metrics for data centres.
Keywords: Database management; Computer system performance; Computer Communication Networks; Computer science; Information Systems; Computer simulation; Database Management; System Performance and Evaluation; Computer Communication Networks; Computers and Society; Management of Computing and Information Systems; Simulation and Modeling